Comparison of drone with remote-controlled sprayer arm and variable rate sprayer for monitoring coconut rhinoceros beetle infestations - Samseemoung, Grianggai; Bhucksasri, Junlaphong; Parnsakhorn, Sunan; Kalsirisilp, Roongruang; Samseemung, Malarin; Jayasuriya, Hemantha PW (Agriculture and Natural Resources, 2023)
Importance of the work: Drones are now widely available, inexpensive, and adaptable. Additional equipment can be used for precision or smart agriculture, especially in the spraying of coconut rhinoceros beetle infestations, and to reduce the risk of direct chemicals. Objectives: To design, fabricate and compare the performance of a remote-controlled sprayer arm with a drone-mounted, variable-rate (VRT) sprayer for rhinoceros beetle monitoring. Image data segmentation was compared by calibrating the altitude of the camera and nozzle. Materials & Methods: The drone used had a payload capacity of 5 kg, weighed roughly 7.85 kg and was flown using a radio transmitter with a range of 1–2 km. The equipment was attached to the sprayer arm, which had a camera and a spray nozzle with a variable spray rate control system. The remote control could be operated from the ground and benchmark comparisons were made with a ground-based variable rate sprayer to determine a working speed, working capacity, spraying rate, electricity consumption and fuel consumption. Results: With a working speed of 1.25 km/hr and a spraying rate of 0.333 L/hr, the drone had a working capacity of 0.352 ha/hr and consumed 0.741 kWhr of electricity. There was a significant correlation between either the normalized difference vegetation index captured by the drone (NDVIDrone) or the green normalized difference vegetation index (GNDVIDrone) and the chlorophyll detected using a chlorophyll meter in both healthy and infected mature coconut trees (Pearson’s correlation coefficient, (r) in the range 0.7885−0.8126). The VRT sprayer had a fuel consumption of 0.58 L/hr, a working capacity of 0.056 ha/hr, and a spraying rate of 162.72 L/hr at a forward speed of 1.5 km/hr for healthy and infected mature coconuts. High correlations were observed between either the normalized difference vegetation index for the sprayer (NDVIVTR Sprayer) or the green normalized difference vegetation index for the sprayer (GNDVIVTR Sprayer) and the chlorophyll content measured using a chlorophyll meter in both healthy and infected trees (r range = 0.8288−0.9595). Main finding: The benefit of using a drone with a sprayer arm was that numerous coconut trees could be sprayed, with less transportation required of chemicals. The drawback of the VRT sprayer was that spraying could only be carried out extremely slowly. However, it had a large chemical carrying capacity.